Evaluasi Keuangan Laporan Komite Sekolah di SMAN 1 Ampek Angkek - Rina Andriyeni; Supratman Zakir; Darul Ilmi (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to evaluate the comparison of school committee financial reports at SMAN 1 Ampek Angkek in the 2022/2023 academic year with the previous year. This research is a comparative research with data collection methods through interviews, observation and document analysis. The results showed1) The similarity in the report is the report column model used. 2) The difference is in the report writing of each activity. In the committee's financial report for the 2022/2023 academic year, the writing is inconsistent. Sometimes it is written with budget details per activity, sometimes it is written in general terms. There were even several activities whose reports were put together by only writing one activity, while in the previous year's committee financial report, the report writing seemed more consistent with the breakdown of funds per activity, 3) The writing of committee financial reports needs improvement.